The Role Of Word Of Mouth’s Value Co-Creation On The Achievement Of Sustainability - Buana, Yud (Jayapangus Press, 2021)
Consumers who buy their products through e-commerce are beginning to pay attention to a company's corporate social responsibility (CSR) status. Due to technological advancements, information became more transparent. Based on this phenomenon, research is required to determine the extent to which word-of-mouth consumers collaborate to increase value in order to achieve sustainability. In this study, the achievements are examined from the perspective of co-creation on the word of mouth aspect, with dimensions of three main factors, namely, social, economic, and environmental. The hypothesis of this study was tested using structural equation modeling (SEM), which includes an assessment of the segments of the related pathways. A total of 297 Indonesians who have completed at least 20 transactions in e-commerce, expressed concern about three important aspects of sustainability: people, profit, and the planet. This finding demonstrates the importance of co-creation of word-of-mouth value in achieving sustainability. Further research into the moderating effects of more detailed aspects of the supporting ecosystem could be conducted in the future.